The Role of Islamic Leadership Style and Affective Commitments to Human Resources Performance at Pt. Indonesian in Health Life Insurance In Semarang - Maritasari, Atik; Widodo, Widodo (Journal of Public Administration and Governance, 2023)
The purpose of this study was to describe and analyze the influence of Islamic Leadership Style on human resource performance, Islamic Leadership Style on affective commitment, and Affective Commitment on human resource performance. The research method uses descriptive statistical analysis method, with a sample of 150 respondents. The results of the study indicate that an increase in Islamic Leadership Style can improve HR performance, which is supported by empirical data. Likewise with Islamic Leadership Style and its effect on increasing Affective Commitment which is supported by empirical data, as well as Affective Commitment which is able to improve HR performance which is supported by empirical data. The conclusion in this study is that there is a relationship between the variables that affect innovative performance, consisting of 2 variables that are proposed and supported empirically, namely: Islamic Leadership Style and Affective Commitment. Managerial implications related to the Islamic leadership style, leaders are considered to need to develop an attitude to attract the attention of employees who have been felt weak by employees. With regard to affective commitment, systematic indicators for improving employee performance are through perceptions of organizational support, paying attention to employee complaints, organizational pride, and organizational concern, and increasing appreciation for the extra efforts of employees. In relation to the performance of human resources, there is a need for appreciation and a relationship with good management.